Management practices to control premature senescence in Bt cotton. (27th August 2017) - Bilal, Muhammad Faisal; Saleem, Muhammad Farrukh; Wahid, Muhammad Ashfaq; Shakeel, Amir; French, Andrew; Sarwar, Muhammad
ABSTRACT: Commercial cultivation of Bt cotton produced higher boll load which led to stiff inter-original competition for photosynthates, resulting in early cessation of growth (premature senescence) due to more availability of sink and less sources. To overcome this problem, field experiment was conducted during 2011 and 2012 using five treatments of plant growth manipulation viz. no fruiting branch removal (F1 ), removal of first fruiting branch (F2 ), removal of first and second fruiting branch (F3 ), removal of all squares from first fruiting branch (F4 ), removal of all squares from first and second fruiting branches (F5 ), and three potassium (K) application rates viz. 50 kg ha −1 (K1 ), 100 kg ha −1 (K2 ), and 150 kg ha −1 (K3 ). More nodes above white flower were recorded in F5, followed by F3, while minimum were recorded in F1 . Among potassium levels, maximum nodes above white flower were recorded in K3 followed by K2 and K1 during both years of study. Plant height recorded at physiological cutout stage or at maturity stage showed that plants gained more height with removal of all squares from first tosecond fruiting branches with higher potassium dose. Leaf K increased with increasing applied potassium and also with square/branch removal. So early removal of squares/fruiting branches along with higher potassium dose helped in delaying canopy senescence in Bt cotton.